When Matter “Speaks”: Matter and Process of Signification Around the Ephemeral Post-attack Memorials of La Rambla in Barcelona - Monforte Rubia, Cristian (E|C, 2023)
Based on three objects from the La Rambla grassroots memorials, created following the jihadists attacks of August 17, 2017, in Barcelona and Cambrils, this article aims to examines the relationship between matter, meaning and significance. By considering these spaces as axes of reconfiguration of the symbolic, as well as the link between meaning and materiality, it is a question here of understanding what are the reserves of meaning specific to these materials, what are the implications of this materiality in the construction meaning and understand how materials participate in the process of memorialization and sacralization of these memorial spaces.